IMPORTANCE OF STRUCTURED VIVA AS AN ASSESSMENT TOOL IN ANATOMY - Naureen Waseem; Khadija Iqbal (Journal of University Medical & Dental College, 2016)
ABSTRACT: Evaluation of students is a vital component of any educational process and it is necessary to improve the performance. Viva voce is an integral part of assessment of medical student. It is of utmost importance to evaluate the tool used to assess the students so that the competencies aimed to achieve in the learner, can be determined. In this study we compared the results of structural viva with an unstructured one in Gross Anatomy. OBJECTIVE: Objective of this study is to compare the performance of 1st year medical students in structured viva of Gross Anatomy, in comparison to unstructured one. DESIGN: Observational trial MATERIAL AND METHODS: Anatomy viva was taken from first year MBBS students at ANMC, Islamabad by both structured and unstructured pattern. The domain selected to be tested were the nerves of upper limb. The specific pattern of structured and unstructured viva was formulated and results of both exams were analyzed and compared. The students were also asked for the feedback about the viva to assess the acceptability of the students. RESULTS: On comparing the results there was statistically significant difference comparing the results of a structured viva with the unstructured one. The result showed that structured viva increases the objectivity and reduces subjectivity in marking, plus the students were overall satisfied and felt structured viva better than the traditional one. CONCLUSION: The marks obtained by the students in conventional and structured viva showed that the structural viva is uniform and reliable method of assessment.